1991
DOI: 10.1128/jvi.65.1.225-231.1991
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of human immunodeficiency virus type 1 nef and long terminal repeat sequences over 4 years in vivo and in vitro

Abstract: The evolution of an 851-bp segment of the human immunodeficiency virus type 1 (HIV-1) genome encoding the nef open reading frame and U3/R elements of the long terminal repeat has been followed over a 4-year period in vivo and in vitro. The population of viral sequences at any given time was established by sequencing cloned polymerase chain reaction products. The samples studied were derived from the same man for whom a detailed analysis of the tat gene was previously described (A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
51
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(58 citation statements)
references
References 35 publications
7
51
0
Order By: Relevance
“…It has been shown previously both in vitro and in vivo that the GA nucleotide substitution is the most frequent. [11][12][13][14][15][16][17][18] In contrast, studies on intrapatient sequence variation of the gag gene found no differences between proportions of GA and AG transitions. [19] A V106M mutation in RT is preferentially selected both in vitro and in vivo by the NNRTI efavirenz in subtype C viruses and confers high-level cross-resistance to all 3 currently approved NNRTIs.…”
Section: G190smentioning
confidence: 99%
“…It has been shown previously both in vitro and in vivo that the GA nucleotide substitution is the most frequent. [11][12][13][14][15][16][17][18] In contrast, studies on intrapatient sequence variation of the gag gene found no differences between proportions of GA and AG transitions. [19] A V106M mutation in RT is preferentially selected both in vitro and in vivo by the NNRTI efavirenz in subtype C viruses and confers high-level cross-resistance to all 3 currently approved NNRTIs.…”
Section: G190smentioning
confidence: 99%
“…Significant genetic variation occurs within the human immunodeficiency virus (HIV) genome [reviewed by Leigh Brown, 19911. Many studies have shown that variation occurs in both a n inter-and intrapatient [Delassus et al, 1991[Delassus et al, , 1992Goodenow et al, 1989;Simmonds et al, 1990;Wain-Hobson, 19921 and that heterogeneity is not evenly distributed throughout the genome [Pedroza Martins et al, 1991, 19921. Thus, the hypervariable regions (Vl-V5) of the enu gene are significantly more heterogeneous than regions of the g a g gene [Leigh Brown and Monaghan, 1988;Balfe et al, 19901. The enu gene contains the principal neutralising determinant of HIV-1 [Rusche et al, 1988;Palker et al, 19881.…”
Section: Introductionmentioning
confidence: 99%
“…Although its mechanism of action is not understood, nefgene function has been shown to be essential for the maintenance of high levels of virus replication and the development of disease pathogenesis in the in vivo model of simian immunodeficiency virus (SIVmac) 1 infection of the macaque monkey (1). In HIV-1 infection of humans, there appears to be selective pressure for retention of highly conserved sequences of nefand an open reading flame (ORF) (2,3). In contrast to these data implying an important role for nefduring in vivo infection, the use of standard cell culture systems to study nef function in vitro has produced a wide spectrum of contradictory results.…”
mentioning
confidence: 99%